George Sword's Warrior Narratives : Compositional Processes in Lakota Oral Tradition - Red Shirt, Delphine, 1957- (Book collections on Project MUSE., 2016)
Published through the Recovering Languages and Literacies of the Americas initiative, supported by the Andrew W. Mellon FoundationThe general focus in Lakota oral literary research has been on content rather than process within oral traditions. In this groundbreaking study of the characteristics of Lakota oral style, Delphine Red Shirt shows how its composition and structure are reflected in the work of George Sword, who composed 245 pages of text in the Lakota language using the English alphabet. What emerges in Sword's Lakota narratives are the formulaic patterns inherent in the Lakota language that are used to tell the narratives, as well as recurring themes and story patterns. Red Shirt's primary conclusion is that this cadence originates from a distinctly Lakota oral tradition. Red Shirt analyzes historical documents and original texts in Lakota to answer the question: How is Lakota literature defined? Her pioneering work uncovers the epistemological basis of this literature, which can provide material for literary studies, anthropological and traditional linguistics, and translation studies. Her analysis of Sword's texts discloses tools that can be used to determine whether the origin of any given narrative in Lakota tradition is oral, thereby opening avenues for further research.